House of cards: on Ken Wilber's neo-traditionalism. (2nd April 2016) - Bazzano, Manu
Abstract : Wilber's writings rely on perennial philosophy and present a traditionalist perspective drawing on selective scholarship. They provide the reader with the illusion of stability and inclusiveness in a field that is instead pluralistic and multi-layered. His perspective is implicitly wedded to political conservatism and to a hierarchical vision of human experience that denies the reality of the body and the transience of life, and is at variance with a progressive counter-tradition and a counter-cosmology whose provisional tenets are highlighted.